The Analysis of Translation Techniques in Translating Fairytale Story “The Adventure of Pinocchio” (English-Indonesian Version) - Nurullah Hairunnisa Latingara; Novriyanto Napu; Jefriyanto Saud (TRANSBAHASA, 2023)
This research aims to analyze the translation techniques employed in the English-Indonesian translation of Carlo Collodi's